Cognitive function in patients with coronary artery disease: A literature review - Burkauskas, J. (J Int Med Res, 2018)
OBJECTIVE: Cognitive function impairment is a well-documented complication of cerebrovascular disease (CBVD). Less is known about what factors affect the deterioration of cognitive function in patients with coronary artery disease (CAD). The aim of this review is to explore recent studies investigating factors associated with cognitive function in patients with CAD. METHODS: Studies published from 2010 to 2016 were identified through a systematic search of MEDLINE/PubMed and were included if they addressed factors affecting cognitive function in the CAD population. RESULTS: Of the 227 publications identified, 32 were selected for the review. Five factors tentatively affecting cognitive function in patients with CAD were identified: coronary artery bypass grafting (CABG) surgery, apolipoprotein E4 (APOE4) genotype, left ventricular ejection fraction (LVEF), medication use, and various hormones and biomarkers. CONCLUSION: New techniques in CABG surgery have proven to alleviate postoperative cognitive decline. Researchers are still debating the effects of APOE4 genotype, LVEF, and the use of cardiovascular medications on cognitive function. Thyroid hormones and biomarkers are associated with cognitive function, but the exact nature of the association is debatable. Longitudinal studies should clarify those associations. In addition, cross-sectional studies addressing other causes of cognitive decline in patients with CAD are warranted.